It is important that the process goes quickly, isn't it?" A qualitative multi-country study of colorectal or lung cancer patients' narratives of the timeliness of diagnosis and quality of care. (June 2018) - Malmström, Marlene; Rasmussen, Birgit H.; Bernhardson, Britt-Marie; Hajdarevic, Senada; Eriksson, Lars E.; Andersen, Rikke Sand; MacArtney, John I.
Abstract: Purpose: The emphasis on early diagnosis to improve cancer survival has been a key factor in the development of cancer pathways across Europe. The aim of this analysis was to explore how the emphasis on early diagnosis and timely treatment is reflected in patient's accounts of care, from the first suspicion of colorectal or lung cancer to their treatment in Denmark, England and Sweden. Method: We recruited 155 patients in Denmark, England and Sweden who were within six months of being diagnosed with lung or colorectal cancer. Data were collected via semi-structured narrative interviews and analysed using a thematic approach. Results: Participants' accounts of quality of care were closely related to how quickly (or not) diagnosis, treatment and/or healthcare processes went. Kinetic metaphors as a description of care (such as treadmill) could be interpreted positively as participants were willing to forgo some degree of control and accept disruption to their lives to ensure more timely care. Drawing on wider cultural expectations of the benefits of diagnosing and treating cancer quickly, some participants were concerned that the waiting times between interventions might allow time for the cancer to grow. Conclusions: Initiatives emphasising the timeliness of diagnosis and treatment are reflected in the ways some patients experience their care. However, these accounts were open to further contextualisation about what speed of healthcare processes meant for evaluating the quality of their care. Healthcare professionals could therefore be an important patient resource in providing reassurance and support about the timeliness of diagnosis or treatment. Highlights: Patients might draw on a wider cultural understanding about the importance of quick treatment when evaluating their care. Patients could choose to forgo some control over their care to achieve an early diagnosis or timely treatment. The difference between patient and HCPs understanding of timeliness can be a source of anxiety for patients. HCPs should ensure they have explicitly addressed individual patient concerns related to timeliness of treatment. Patients understanding of timeliness of treatment may change during the health care pathway.